Pilgrimage to a memory hole towards an affective study of fan tourism in Asia via Angkor Wat and Wong Kar-wai’s In the Mood for Love - Promkhuntong, Wikanda (Plaridel, 2019)
Access online through this link: https://www.plarideljournal.org/article/pilgrimage-to-a-memory-hole-towards-an-affective-study-of-fan-tourism-in-asia-via-angkor-wat-and-wong-kar-wais-in-the-mood-for-love